Hubungan Bersyukur dengan Kesejahteraan Subjektif pada Orang Tua yang Memiliki Anak Tunagrahita di SLB Negeri 2 Kota Padang - Murisal, Murisal; Hasanah, Trisna (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2017)
This study aims to determine the relationship between gratitude and subjective well-being of parents who have mentally retarded children in SLB Negeri 2 Padang. The measuring instrument in this research is a psychological scale that reveals aspects of the research in the form of statement items. Data were collected using two scales, namely the thankful scale and the subjective welfare scale. The scale of gratitude is referred to from Al-Ghazali's theory whose operation is based on the interpretation of the verses concerning gratitude. Whereas the scale of subjective well-being is referred to from the theory of diener which states that subjective well-being consists of two dimensions, namely affective and cognitive. The subjects in this study were parents who have mental retardation children in SLB Negeri 2 Padang, amounting to 83 people. The data collection technique in this research is to use simple random sampling which means that each subject has the same opportunity to be chosen. The results of the correlation analysis showed a relationship between gratitude and subjective well-being among parents who have intellectual disabilities in SLB Negeri 2 Padang. The correlation coefficient of the results of data analysis amounted to 0.156 (rxy = 0.516 p <0.05). The general description of the research data shows that the thankful level of parents of mentally retarded children is included in the high criteria with a percentage of 56% and the high subjective well-being of mentally retarded children at 62%. This means that the mentally retarded child's parents are able to be enthusiastic in educating their children and accepting their child's condition gracefully.